The Respons Growth of Pepper cuttings On Concentration and Duration of Immertion in Rootone-F - Sri Mulatsih; Sri Rustianti; Dewi Sartika (University of Prof. Dr. Hazairin, SH, 2022)
The aim of the study was to determine the effect of concentration, soaking time in rootone-F and the interaction between concentration and soaking time in rotoone-F on the growth of pepper cuttings (Piper nigrum L.). The design used was a Randomized Block Design (RAK) with two factors and three replications. The first factor is the concentration of Rootone-F with 4 levels (K0: without rootone-F; K1: concentration of 100ppm; K2: concentration of 200 ppm and K3: concentration of 300 ppm). The second factor is the length of immersion in rootone-F with 3 levels (P1: soaking time for 1 hour; P2: soaking for 2 hours; P3: soaking for 3 hours). The variables observed were the number of shoots, shoot height, number of leaves and root length. The results showed that concentration had a significant effect on shoot height, the length of immersion in rootone-F had no significant effect on all observed variables. The interaction between concentration and soaking time in rootone-F had no significant effect on root length, significantly on number of shoots and number of leaves and very significant effect on shoot height. The best growth of pepper cuttings was at a concentration of 300 ppm with a soaking time of 3 hours which was shown from the shoot height and the highest number of shoots.